Breeding perennial species for abiotic stress - De Paula, Rinaldo Cesar [UNESP]; De Paula, Nadia Figueiredo; Marino, Celso Luis [UNESP] (Springer Nature, 2012)
In agriculture, the term stress is understood to mean any factor, whether biotic or abiotic, that is detrimental to the growth and productivity of plants. Managing stress caused by climatic events, especially in large perennial species occupying extensive cropping areas, is in most cases neither technically nor economically viable. In this chapter we will approach the breeding of perennial species tolerant to abiotic stress based on studies of Eucalyptus under water deficiency conditions, the most common stress factor in areas used for cultivating this genus in Brazil. The forestry breeding programs conducted in Brazil have been primarily directed toward growth traits, and more recently, wood quality. Indirectly, there has been selection, albeit unintentional, for adaptation to the environmental conditions under which commercial companies operate, and it can be assumed that drought-tolerance characteristics have not been fully explored in these programs. As new forest frontiers have opened up in regions with limited water resources, the search for productive and therefore drought-tolerant genotypes should be a key feature in breeding programs. Since the species concerned are perennials with a long life cycle, during their development the plants pass through innumerable situations that are unfavorable to growth. In contrast to short-cycle species, trees cannot avoid these conditions. This means that the mechanisms for withstanding abiotic stress factors in perennial species may be more complex and primarily aimed at species survival, to the detriment of productivity. Understanding these mechanisms is essential for success of a forest breeding program for regions subject to drought.
Keywords: Drought tolerance; Eucalyptus; Tree breeding; Water stress